2013
DOI: 10.3109/19401736.2013.770490
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation amongClonorchis sinensisisolates from different hosts and geographical locations revealed by sequence analysis of mitochondrial and ribosomal DNA regions

Abstract: The present study examined genetic variability among Clonorchis sinensis isolates from four different geographical localities (Guangzhou, Nanning, Jiamusi and Daqing) and host species (cats, dogs, human and rabbits) in Mainland China by sequence analyses of two mitochondrial DNA (mtDNA) genes, namely NADH dehydrogenase subunits 2, 5 (nad2 and nad5) and ribosomal internal transcribed spacer 1 (ITS1). A portion of the ITS1, nad2 (pnad2) and nad5 (pnad5) was amplified by polymerase chain reaction separately from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Although these aspects of the epidemiology of clonorchiasis (transmission and prevalence) are relatively well understood [4,8], there is little comprehensive information on the genetics of C. sinensis and what impact genetic variation within and among populations has on the biology and transmission of C. sinensis infection and the severity of clonorchiasis and/or associated cancer. Published population genetic studies conducted using selected genetic markers, including the internal transcribed spacers (ITS-1 and/or ITS-2) of nuclear ribosomal DNA and the mitochondrial cox1 gene regions, have indicated variable levels of genetic variation and sub-structuring within C. sinensis populations [13][14][15][16][17][18][19][20][21][22]. Other studies have reported draft nuclear genomes of C. sinensis from Korea and China [23,24] and four mitochondrial genomes of individual isolates from Korea, China and the Russian Far East [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Although these aspects of the epidemiology of clonorchiasis (transmission and prevalence) are relatively well understood [4,8], there is little comprehensive information on the genetics of C. sinensis and what impact genetic variation within and among populations has on the biology and transmission of C. sinensis infection and the severity of clonorchiasis and/or associated cancer. Published population genetic studies conducted using selected genetic markers, including the internal transcribed spacers (ITS-1 and/or ITS-2) of nuclear ribosomal DNA and the mitochondrial cox1 gene regions, have indicated variable levels of genetic variation and sub-structuring within C. sinensis populations [13][14][15][16][17][18][19][20][21][22]. Other studies have reported draft nuclear genomes of C. sinensis from Korea and China [23,24] and four mitochondrial genomes of individual isolates from Korea, China and the Russian Far East [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most published molecular evidence seems to suggest that C. sinensis represents a single species and that genetic variation within the species is relatively low (Park and Yong, 2001;Lee and Huh, 2004;Petney et al, 2013). However, to date, most studies have used a relatively small number of genetic loci for specific identification (e.g., internal transcribed spacers of nuclear ribosomal DNA) and/or population genetic studies (e.g., act, tub, ef-1a, cox1, cox3, nad4 and nad5) (Park and Yong, 2001;Lee and Huh, 2004;Liu et al, 2007;Park, 2007;Katokhin et al, 2008;Lai et al, 2008;Shekhovtsov et al, 2009;Liu et al, 2012;Shin et al, 2013;Sun et al, 2013;Tatonova et al, 2013;Xiao et al, 2013;Chelomina et al, 2014), and it is not yet known whether "cryptic" (= morphologically similar, but genetically distinct) species exist within C. sinensis. Nonetheless, karyotypic differences in C. sinensis observed among China, Korea (2n = 56) and the Russian Far East (2n = 14) (Park and Yong, 2001;Zadesenets et al, 2012) do suggest that this might be the case.…”
Section: Introductionmentioning
confidence: 99%
“…The CsM33 marker is the most polymorphic (11 alleles), while CsM26 had only 2 alleles. Variation of microsatellites in our study mainly differ in the repeat numbers while other genetic markers, such as rDNA or mtDNA, the difference is in its sequence (Lee and Huh 2004; Liu et al 2012; Xiao et al 2013). …”
Section: Discussionmentioning
confidence: 64%
“…Infection with this liver fluke can lead to several hepatobiliary diseases including cholangiocarcinoma as it is classified as a Group I carcinogen by the International Agency for Research on Cancer, WHO (Bouvard et al 2009; Hong and Fang 2012). Since the parasite is distributed over a half of Asia, genetic diversity in the endemic regions has been reported using conventional molecular markers such as mtDNA and rRNA (Lee and Huh 2004; Liu et al 2012; Park 2007; Tatonova et al 2012; Tatonova et al 2013; Xiao et al 2013). These genetic variations of C. sinensis may influence disease presentation, host specificity and other biological functions (Choi 1984; Saijuntha et al 2007; Hong and Fang 2012; Sun et al 2013).…”
Section: Introductionmentioning
confidence: 99%